Measured calorimetrically effects of cosmic radiation on the average latitude - Dyachkov, V.V.; Zaripova, Y.A.; Naurzbaeva, A.Zh.; Sysoev, V.A.; Shakirov, A.L.; Yushkov, A.V. (Recent Contributions to Physics, 2013)
Detect and measure the calorimetric effect from cosmic radiation (CR) using the experimental setup. Designed and manufactured laboratory prototype of energy cell and thermal measurements performed using as thermal benchmark elements: air, water, and liquid nitrogen. In this paper the authors, on the model of volume of 1 liter, demonstrated the existence of a calorimetric effect of space quantum radiation. It was found that the primary calorimeter effect may register only under special conditions, because of its small size for such a working fluid, which is very far from the "critical". By "critical" means that amount of working fluid power module, in which the heat loss is much lower heat accumulated in the power module. To test the efficiency installation as a whole and its absolute calibration in this paper is primarily determined by calorimetric effect of simulating gauge alpha sources.